Education and Economic Growth in Nepal: An ARDL Approach - Duwal, Niroj; Acharya, Anjana (Economic Journal of Development Issues, 2023)
Education increases the quality and the quantity of human capital stock. The endogenous growth theory emphasizes the role of education in the economic growth. This study investigates the relationship between education and economic growth in Nepal using time series data from 1986 to 2022 in ARDL model. This study considers GDP growth as the dependent variable and growth in gross fixed capital formation, change in total population of ages 15 to 64, growth in government expenditure on education, school enrollment in secondary level, school enrollment in tertiary level and inflation rate as independent variables. The results show the existence of a long-run relationship between gross fixed capital formation and GDP positively and significantly. The government expenditure on education, school enrollment in secondary level, and inflation have insignificant and negative relation with GDP growth. Total population and school enrollment in tertiary level have positive and insignificant relation with GDP growth. In short run, total population have dynamic effects in Nepalese economy. This study suggests that there should be more studies considering other proxies to support the unavoidable evidence of education as the backbone of any economy.